IMPLEMENTASI ELEMEN-ELEMEN DESAIN YANG DITERAPKAN PADA PERANCANGAN DESAIN FASHION REUSABLE BAG - OLIVIA GONDO PUTRANTO (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2018)
Recently environmental problem becomes a highlight, and bought out to the surface, mostly about plastic waste and how to deal with it. When plastic waste dissolved they released some kind of toxic substances that will harm the environment and bring damage to the ecosystem. In order to reduce the mass volume of plastic waste, the Indonesian Government made some regulations. One of the regulation stated that the customer had to pay for the plastic bag each time they had transactions. But this program didnâ€™t last a long time because of some pros and cons about the regulation. PT. Lion Super Indo, or known as Super Indo Supermarket is one of the brands that applying sustainability movement as their main strategy. One of their programs is to create a competition for designing Fashion Reusable Bag in order to educate Indonesian people to get used to bring and use reusable bag everytime they shop. This research using literature studies and using descriptive qualitative as a method, divided into two phase. The first phase is the literature studies for the indicators used in this research, the elements of design and the judging aspects of the competitions. The Judging aspects are Uniqueness, Brand, Fashion, and Practicality. The next phase is a single case study with an implementation of Design Elements and Judging Aspects. Hopefully, the findings and the result of this research could help to take apart bringing more impact of the sustainability movement and give some contribution in order to reduce plastic waste volume in Indonesia.Â